Remarks on Common Fixed Point Results in \(C^*\)-Algebra-Valued Metric Spaces - Dey, Lakshmi Kanta; Senapati, Tanusri (Journal of Informatics and Mathematical Sciences, 2018)
In this short note, we study the article of Xin et al. [J. Nonlinear Sci. Appl., (9) 2016] and unexpectedly notice that the common fixed point results of this article do not produce any new result in literature. In fact the main results of this article coincide with some consequences of previous published results.